Roux-en-Y gastrectomy. A 12 years’ experience. - Fernandes, F V; Reis, C; Mascarenhas, L; Branco, A B (Acta Médica Portuguesa, 1990)
A review of 161 patients who underwent Roux-en-Y biliary diversion and truncal vagotomy from 1978 to 1989 is performed under the double perspective: clinical and functional (using radionuclide semi-solid and liquid gastric emptying (GE) studies). In 46 patients this solution was adopted to treat different kinds of post-gastrectomy syndromes and in 115 to solve the esophageal-duodeno-gastric peptic disease. Some technical details are considered very important to prevent the nominated post Roux-en-Y Syndrome in relationship with the gastroparesis and gastric retention. The overall operative mortality was 2.5%. Five patients were reoperated: two, to complete vagotomy; 2, to solve gastric retention and one with sub-occlusion due to jejunal stricture. Forty one patients with 7.4 +/- 1.3 years after surgery were graded Visick I or II in 82.9% of the cases and 17.1% Visick III or IV. Gastric emptying studies demonstrated that the problems of gastric fullness detected in the immediate post operative period are quite similar to those observed after other kinds of sub-total gastrectomies. After 6 months, the gastric emptying change to a more rapid pattern in the large majority of patients. In the late post operative period is quite common to have no agreement between gastroparesis complains and the objective measurements of the GE, in symptomatic patients. Roux-en-Y gastrectomy solve the problems of post gastrectomy syndromes in 80% of the cases and in our experience, is a method that can be used with advantage to treat the ulcerative peptic disease resistant to the medical treatment in patients with less than 50 years.